Metal ions as antibacterial agents - Mittapally, Sirisha; Taranum, Ruheena; Parveen, Sumaiya (Journal of Drug Delivery and Therapeutics, 2018)
Metals like mercury, arsenic, copper and silver have been used in various forms as antimicrobials for thousands of years. The use of metals in treatment was mentioned in Ebers Papyrus (1500BC); i.e, copper to decrease inflammation & iron to overcome anemia. Copper has been registered at the U.S. Environmental Protection Agency as the earliest solid antimicrobial material. Copper is used for the treatment of different E. coli, MRSA, Pseudomonas infections. Advantage of use of silver is it has low toxicity to human’s cells than bacteria.It is less susceptible to gram +ve bacteria than gram –bacteria due to its thicker cell wall. Zinc is found to be active against Streptococcus pneumonia, Campylobacter jejuni. Silver & zinc act against vibrio cholera & enterotoxic E. coli. The use of metals as antibacterial got reduce with discovery of antibiotics in twentieth century, immediately after that antibiotic resistance was seen due to transfer of antibiotic resistance genes by plasmids also known as Resistance Transfer Factors or R-factors. Metal complexes are used to show synergistic activity against bacteria’s like copper & chlorhexidine on dental plaque bacteria, silver nanoparticles & cephalexin against E. coli & S. aureus.Keywords: Metals, Oligodynamic effect, Copper, Silver